PENGUKURAN KINERJA UNIT KERJA PEMERINTAH DAERAH DENGAN PERSPEKTIF VALUE FOR MONEY - Setiyawati, Yuly Indah; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the work performance model of the implementation of program andactivity on Dinas Pendidikan Kabupaten Sidoarjo which is carried out by using the Value for Moneyperformance measurement perspective. The descriptive qualitative is used as the data analysis technique which isdone by collecting, processing, and presenting the data that has been obtained in the form of complete andaccurate information, so the researcher is easier to gain description about the characteristic of this object. Thedata collection technique has been done by performing interview and documentation.Based on the result of theresearch, it shows that Dinas Pendidikan Kabupaten Sidoarjo has successfully achieved the expected efficient andeffective economic level. The economic performance is smaller than the budget when it is considered from theamount of the realization. The efficiency of the performance can be seen from the comparison between the inputand the output in which the work plan program and institution activities can be achieved and realized inaccordance with the planned target. Meanwhile the effectiveness of the performance can be seen from the resultsof the achievement of target performance indicators in achieving an organizations objective in which the resultsof activities to achieve the objective can be realized in accordance with the expected targets. Although theefficiency and effectiveness of the economic performance of Dinas Pendidikan Kabupaten Sidoarjo has beenreached, however, the development of the Value for Money performance indicator is still required, so it canexplain the achievement of the performance of Dinas Pendidikan Kabupaten Sidoarjo comprehensively.Keywords:Performance, Value For Money, Economic, Efficiency, Effectiveness.